2013
DOI: 10.1172/jci66028
|View full text |Cite
|
Sign up to set email alerts
|

Evolving therapies for liver fibrosis

Abstract: Fibrosis is an intrinsic response to chronic injury, maintaining organ integrity when extensive necrosis or apoptosis occurs. With protracted damage, fibrosis can progress toward excessive scarring and organ failure, as in liver cirrhosis. To date, antifibrotic treatment of fibrosis represents an unconquered area for drug development, with enormous potential but also high risks. Preclinical research has yielded numerous targets for antifibrotic agents, some of which have entered early-phase clinical studies, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
529
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(542 citation statements)
references
References 167 publications
3
529
0
4
Order By: Relevance
“…Factors associated with inefficient fibrolysis in the liver include advanced vascular remodeling with architectural distortion, extensive cross-linking of ECM components hindering proteolytic removal, and the disappearance of cells that digest and degrade scar tissue. 6 Chronic infection with hepatitis C virus is a common cause of liver fibrosis, and the most compelling evidence that spontaneous resolution of fibrosis is possible in humans comes from studies examining the response to antiviral treatments. There is clear histological evidence from biopsy tissue of patients with mild-to-moderate fibrosis who are successfully treated for hepatitis C virus infection indicating resolution of the fibrosis seen in the index biopsy.…”
Section: Reversibility Of Tissue Fibrosismentioning
confidence: 99%
“…Factors associated with inefficient fibrolysis in the liver include advanced vascular remodeling with architectural distortion, extensive cross-linking of ECM components hindering proteolytic removal, and the disappearance of cells that digest and degrade scar tissue. 6 Chronic infection with hepatitis C virus is a common cause of liver fibrosis, and the most compelling evidence that spontaneous resolution of fibrosis is possible in humans comes from studies examining the response to antiviral treatments. There is clear histological evidence from biopsy tissue of patients with mild-to-moderate fibrosis who are successfully treated for hepatitis C virus infection indicating resolution of the fibrosis seen in the index biopsy.…”
Section: Reversibility Of Tissue Fibrosismentioning
confidence: 99%
“…Toll-like receptors (TLR2 and TLR4) have been linked to hepatic infl ammation and fi brosis (47)(48)(49)(50). We previously reported that feeding Ldlr Ϫ / Ϫ mice the WD increased plasma endotoxin ( 18 ), a gut-derived microbial factor that activates the TLR4 pathway ( 51 ).…”
Section: Effect Of the Wd And 3 Pufa On Plasma Factors Linked To Hepamentioning
confidence: 99%
“…Myofibroblasts derived from HSC are the primary effector cells in liver fibrosis [49][50][51], whereas hepatocytes and cholangiocytes work in coordinated fashion to secrete bile [52] and are primary targets of a variety of liver diseases [53,54] . Isolation of HSC, hepatocytes, and cholangiocytes is now technically straightforward [55], yet there are good reasons to use cell culture models of each of these cell types.…”
Section: Ecto-nucleotidasesmentioning
confidence: 99%